2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1326055
|View full text |Cite
|
Sign up to set email alerts
|

Automatic emotional speech classification

Abstract: Our purpose is to design a useful tool which can be used in psychology to automatically classify utterances into five emotional states such as anger, happiness, neutral, sadness, and surprise. The major contribution of the paper is to rate the discriminating capability of a set of features for emotional speech recognition. A total of 87 features has been calculated over 500 utterances from the Danish Emotional Speech database. The Sequential Forward Selection method (SFS) has been used in order to discover a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
2

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 2 publications
1
89
0
2
Order By: Relevance
“…Currently there are two main approaches to affective computing: Audio-based techniques to determine emotion from spoken word are described for example in [4,5,6] and video-based techniques that examine and classify facial expressions are described in [7,8,9]. More advanced systems are multi-modal and use a variety of microphones, video cameras as well as other sensors to enlighten the machine with richer signals from the human [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are two main approaches to affective computing: Audio-based techniques to determine emotion from spoken word are described for example in [4,5,6] and video-based techniques that examine and classify facial expressions are described in [7,8,9]. More advanced systems are multi-modal and use a variety of microphones, video cameras as well as other sensors to enlighten the machine with richer signals from the human [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The Student t-test for unequal variances has also found that the differences in the average assignment ratio per emotion are statistically significant for a 15-fold cross validation experiment. Figure 1 depicts a partition of the 2D feature domain that has been resulted after selecting the five best emotional features by the Sequential Forward Selection algorithm and applying Principal Component Analysis in order to reduce the dimensionality from five dimensions (5D) to two dimensions (2D) [16]. Only the samples which belong to the interquartile range of the probability density function for each class are shown.…”
Section: Resultsmentioning
confidence: 99%
“…A number of 1160 emotional speech patterns are extracted. Each pattern consists of a 90-dimensional feature vector [16]. Each emotional pattern is classified into one of the five primitive emotional states, such as hot anger, happiness, neutral, sadness, and surprise.…”
Section: Datamentioning
confidence: 99%
“…To obtain the statistics of energy feature, we use short-term function to extract the value of energy in each speech frame. Then we can obtain the statistics of energy in the whole speech sample by calculating the energy, such as mean value, max value, variance, variation range, contour of energy [6].…”
Section: Energymentioning
confidence: 99%